Optimal cross-layer power allocation with channel and queue state information - CHEN Wei1; CAO Zhi-gang1; FAN Ping-yi1; LETAIEF K B2 (Tongxin xuebao)
The optimal power allocation was investigated when both channel and queue state information was taken into account.By modeling the system from a cross-layer perspective,an optimization problem was formulated on power allo-cation where the maximal power requirement of a user was determined by the number of its backlog packets.The ana-lytical solution as well as its algorithm,which refer to as water filling in cellar（WFIC）,were proposed.The proposed WFIC can be reduced to traditional water-filling（TWF） method as a special case where queue state was ignored.Simula-tion results show that the proposed method can achieve lower queuing delay compared to conventional methods.